SMALL ENTERPRISES: KEY SOURCE OF EMPLOYMENT AND ECONOMIC GROWTH - Tihomir Spremo; Jelena Mićić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2015)
Small enterprises, within the market economy, are initiators of economic development and an important part of every national economy. Due to the nature of private property, entrepreneurial spirit, flexibility and adaptability, as well as their potential to react to the challenges and turbulences in the environment, small businesses give a special contribution to economic growth and higher employment. Entrepreneurship and small business represent a significant and fundamental source for creation of new jobs and expansion of new business practices by providing a significant contribution to economic growth. This applies both to small businesses in the Republic of Srpska and the ones that are located anywhere in the world. The role of small enterprises is especially important in transition countries. During the global economic crisis, small businesses have, both in developed economies, and in the Republic of Srpska and BiH as a whole, proved to be resilient, although this period was characterized by a very poor business environment. The importance of entrepreneurship and small firms in developing national economies are often the subject of professional and empirical discussion. However, recent developments have further confirmed the views that small businesses, in dealing with all the negativities of poor business environment in times of crisis, more quickly adapt to changes compared to larger enterprises and companies. This quality of small enterprises gives enough reason to pay special attention to the theoretical and practical aspects of this phenomenon, in order to make appropriate business decisions and implementation of development policy as a more efficient model for faster economic development of the national economy. The subject of this paper is to define the importance of small businesses in the economic growth of developed and developing countries. Through researching analyses, this paper examines the role and importance of small enterprises in economies of the European Union (EU) member states and the Republic of Srpska and BiH, especially regarding its influence on the employment growth and added value in a period of economic crisis and postcrisis years. This paper aims to explore and emphasize the interdependence between growth of small firms and new added values, reviewing economic development and employment in both developed and economies in transition. This paper attempts to present the importance of effects of analyzed economic indicators as a result of small enterprises in two separate periods (the period of global crisis and postcrisis period) and provide guidance and recommendations to policy makers on economic role of small firms in macroeconomic stability of the economy.